Pembentukan Organisasi Cemerlang: Pandangan Islam dalam Melantik Pemimpin - Ismail, Solahuddin (Jurnal Usuluddin, 2009)
A good leadership is the most important element in organization. The organization should be lead by good leaders as these people have the ability to run the organization with the spirit of accountability to fulfill the employee’s expectation. Islam has a perfect way in introducing and producing excellent leaders. Islam believes that a good leader should have a clear mission and a specific goal in managing the organization successfully. The philosophy of good leadership in Islam means one should not only be excellent in the organization but must also excellent in ‘akhirat’. A good Islamic leader should always have the ability in making the organization excellence.